2018
DOI: 10.1016/j.ejrad.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative MRI in post-operative paediatric cerebellar mutism syndrome

Abstract: Post-operative paediatric cerebellar mutism syndrome (pCMS) occurs in around 25% of children undergoing surgery for cerebellar and fourth ventricular tumours. Reversible mutism is the hallmark of a syndrome which comprises severe motor, cognitive and linguistic deficits. Recent evidence from advanced neuroimaging studies has led to the current theoretical understanding of the condition as a form of diaschisis contingent on damage to efferent cerebellar circuitry. Tractography data derived from diffusion MRI st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 78 publications
1
19
0
Order By: Relevance
“…Numerous studies have been undertaken to evaluate the changes in cerebellar structure and connectivity in patients who have experienced PFS (Morris et al, 2009; Patay et al, 2014; Avula et al, 2016; Toescu et al, 2018a, b). An evaluation of factors predisposing medulloblastoma patients to development of PFS found that tumor location proximal to the SCP made development of PFS more likely (Morris et al, 2009).…”
Section: The Cerebellum In Human Affective and Cognitive Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have been undertaken to evaluate the changes in cerebellar structure and connectivity in patients who have experienced PFS (Morris et al, 2009; Patay et al, 2014; Avula et al, 2016; Toescu et al, 2018a, b). An evaluation of factors predisposing medulloblastoma patients to development of PFS found that tumor location proximal to the SCP made development of PFS more likely (Morris et al, 2009).…”
Section: The Cerebellum In Human Affective and Cognitive Diseasesmentioning
confidence: 99%
“…This dentatorubro-olivary loop is referred to as the triangle of Guillain and Molleret. While the debate on the mechanisms involved in the development of PFS are not resolved, there is a significant and growing body of literature implicating disruption of the cerebellar efferent pathways (Toescu et al, 2018a).…”
Section: The Cerebellum In Human Affective and Cognitive Diseasesmentioning
confidence: 99%
“…Although the general tendency is for mutism to slowly improve by way of dysarthria, speech rarely returns to normal. 8 In our cases, the second patient developed symptoms of CMS three days after surgery although impaired neurological symptoms appeared one week later in patients 1 and 3. The broad incidence rate of CMS suggests that some patients are at no or low risk of CMS, and others have a 40–50% risk.…”
Section: Discussionmentioning
confidence: 42%
“…[19][20][21] Imaging studies showing decreased cortical perfusion 22 and disruption of the cerebello-thalamo-cerebral WM tracts on DTI 23 after cerebellar surgery support diaschisis as the mechanism underlying PFS, occurring in 39%-40% of children with medulloblastoma, with a mean latency of 1.7 days. 24 Pathologic studies of brain injury in animals show inflammation and hydropic changes in remote diaschisis lesions. 20,21 Such changes in the ST brain would be expected to reduce myelin density and, therefore, MTR.…”
Section: Discussionmentioning
confidence: 99%